POLA DAN DINAMIKA PENGINJILAN RASUL PAULUS: STUDI TEMATIK BIBLIKAL BERDASARKAN KISAH PARA RASUL - Iwan Setiawan; Yuliana Lu; Zummy Anselmus Dami (Sekolah Tinggi Teologi Arastamar Bengkulu, 2026)
Evangelism was preaching the Good News about Christ. Preaching the Gospel is the responsibility of every believer and church. The church still has not fulfilled its mandate to make disciples. Most churches already know that they must preach the Gospel to all people who do not believe, but they only know but do not try to go to preach the Gospel, so preaching the Gospel is not the main thing.This research aimed to find the basis, area, strategy, principles and impact of evangelism contained in the Acts of the Apostles. The research method used is a qualitative approach with an analytical description method, explaining it in a hermeneutic way. The research results are: The research results obtained based on the book of Acts of the Apostles regarding evangelism were the basis of the apostle Paul's evangelism, namely the inclusion of the holy spirit, the Bible or the gospel of Christ, the commandment or great commission. area of ​​evangelism, exemplary for evangelism, Paul’s evangelism strategy was preaching among his tribes, telling the chronology of the salvation of the Israelites, going to areas, and forming an evangelism team. Principles of Evangelism and Impact of Evangelism